Modern Transformation of Spatial Typology of Shopping Centers - Borysenko Artem (Architecture, Civil Engineering, Environment)
Article focuses on the modern transformation of spatial typology of shopping centers, or malls. In light of an on-going crisis of brick-and-mortar shopping centers, accentuating visitor’s experience in their physical environment becomes a promising trend, while analysis shows that recreational communication space serves as an important factor of their modern spatial transformation. Such a space defines the mode of connection of functional parts of a shopping center, acting as the structure-forming element to a mixed-use system. It also supports non-commercial, public functions, and serves as the driver of visitor’s experience, influencing it through its architecture. Modern transformation of spatial typology of shopping centers highlights the continuing specialization of their types suitable for different roles in contemporary situations. Thus, the semantic and architectural articulation of recreational communication space in the design process is crucial for emphasizing the specifics of a particular spatial type of a modern shopping center, and can help in forming its distinct sense of place in visitor’s perception.